Simulación del Proceso de Absorción Química con soluciones de Aminas para la purificación de biogás - Morero, Betzabet del Valle (2013)
The influence of some key operating parameters and of different types of amines in biogas purification is analyzed. For this a conventional single-loop absorber-stripper process configuration was simulated using four types of amines (monoethanolamine, diethanolamine, diglycolamine and methyldiethanolamine) and two mixtures of them. The process simulator ProMax® was used. The variables studied were methane, carbon dioxide, hydrogen sulphide and water concentrations in the sweetened gas, process energy consumption, absorption temperatures and reboiler steam rates. The simulation results showed good levels of purification in all cases with best results for diglycolamine (97.3% de CH4) which also has the lowest reboiler energy consumption. Prior knowledge of natural gas absorber-stripper processes allowed using the technology in the particular case of biogas.